Neuroimaging and neurodevelopmental outcome of preterm infants with a periventricular haemorrhagic infarction located in the temporal or frontal lobe. (10th February 2014) - Soltirovska Salamon, Aneta; Groenendaal, Floris; van, Ingrid C; Rademaker, Karin J; Benders, Manon J N L; Koopman, Corine; de, Linda S
<x xml:space="preserve">Abstract</x> Aim The aim of the study was to compare clinical and neuroimaging characteristics and neurodevelopmental outcome in preterm infants with a periventricular haemorrhagic infarction (PVHI) located in the temporal or frontal periventricular white matter. Method The study was a retrospective hospital‐based study of preterm infants with a frontal PVHI (n=21; 11 males, 10 females; mean birthweight 1527g; mean gestational age 30.3wks) or temporal PVHI (n=13; five males, eight females; mean birthweight 1205g; mean gestational age 30.2wks) admitted to the neonatal intensive care unit between 1990 and 2012. The clinical course, results of neuroimaging studies, and neurodevelopmental outcomes of preterm infants with a gestational age less than 34 weeks with a confirmed PVHI on early cranial ultrasonography and/or magnetic resonance imaging were reviewed. For assessment of neurodevelopmental outcome we used the Griffiths Mental Development Scales, the Movement Assessment Battery for Children, the Gross Motor Function Classification System, the Wechsler Preschool and Primary Scale of Intelligence, the Child Behavior Checklist, and ophthalmological assessment. An unfavourable neurodevelopmental outcome was defined as moderately or severely atypical neurological examination during the last visit: presence of cerebral palsy, epilepsy, a hearing or visual impairment, and/or atypical cognitive development (Griffiths Mental Development Scales developmental quotient or Wechsler Preschool and Primary Scale of Intelligence <85). Results Unfavourable outcome was observed in 12 out of 13 children with a temporal PVHI compared with six out of 21 children with a frontal PVHI (p=0.002). Only one of the included infants with a PVHI in the temporal white matter developed cerebral palsy, which was due to a parietal PVHI in the contralateral hemisphere. Cognitive impairment was noted in seven infants with a frontal PVHI and five with a temporal PVHI. There were more infants with a temporal PVHI who developed visual impairment (n=5) or behavioural problems (n=7) compared with those with a frontal PVHI (visual impairment (n=2), behavioural problems (n=3). Interpretation PVHI located in the temporal or frontal lobe is almost invariably related to a typical motor outcome, but carries a risk of cognitive, behavioural, and visual problems, especially in infants with a PVHI located in the temporal lobe.